The effect of stress on egg quality in farmed Atlantic Cod (Gadus morhua L.) - Natário, Silvestre Ramos (2011)
Dissertação de mestrado, Aquacultura, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2011 The Atlantic cod (Gadus morhua), is a prestigious species of fish that belongs to the Gadidae family, and is considered a promising species for future aquaculture in the northern hemisphere. Cod production has grown exponentially since the beginning of the millennium. The but development of cod farming has been hampered by bottlenecks in the production such as deformities, diseases as francisellosis, slow growth and early maturation, and in addition relatively low market prices compared to present production costs. Farming of cod relies on a stable supply of high quality eggs. Egg quality and production is dependent not only upon the female condition and hence broodstock diet, but can be negatively affected by stress. In addition, farmed females often fail to release their eggs, become eggbound and die. The project “Why do Atlantic cod females become eggbound? Studies on possible causes and mechanisms” (Research Council of Norway, grant no 190187/E40) investigates the physiological events during normal and abnormal (eggbound) spawning, with the aim to determine factors that may cause the problems. Two factors that may affect these are investigated in this project; The first is dietary lipid content as this correlates to gonadosomatic index (GSI, gonad weight as % of total weight). The fecundity of farmed cod is about 50% higher than wild cod, and one could suspect that abnormally large gonads would increase the problems with eggbound females. The second variable is stress, either directly due to distorted spawning behaviour or indirectly through the eicosanoid cascade. Eggs of poor quality can have a negative impact on production resulting in slow growth, high mortality rate and deformities. In this master it has been focused on the egg production from farmed cod fed either a high (20%) or a low (13%) fat diet, and either physically stressed or not. The stress treatment, imposed randomly once a week, ...